Legal Aspects Of The Act Gambling Crime Online - Wijaya, Krista; Borman, M. Syahrul; Hartoyo, Hartoyo (Ipso Jure, 2025)
: Gambling is a game where players bet using money to choose one option among several options where only one option is correct and becomes the winner. Law enforcement against gambling is not optimal, gamblers and bookies are not punished in accordance with applicable law, even though gambling is clearly a criminal act that is against the law in Indonesia. The problem in this research concerns the legal aspects of online gambling based on Law Number 19 of 2016 concerning Electronic Information and Transactions and what are the inhibiting factors in law enforcement against online gambling based on Law Number 19 of 2016 concerning Electronic Information and Transactions. This research uses a normative research method. Research Results and Discussion: Legal aspects of online gambling have been regulated by Law Number 19 of 2016 concerning Information and electronic transactions and are enforced by law by carrying out preventive and repressive efforts. Inhibiting factors in law enforcement against online gambling are the legal factors themselves, human resource factors, infrastructure and facilities factors and community factors. The conclusion and suggestion in this research is that prevention efforts are needed by blocking sites that contain gambling content as part of the police's efforts to eradicate criminal acts of online gambling. Law enforcers must provide more information to the public about the dangers of online gambling crimes.